Seagrass Biodiversity and its Drivers in the Kepulauan Banyak Marine Nature Park, Indonesia - Nasution, Muhammad Arif; Hermi, Rudi; Heriansyah, Heriansyah; Lubis, Friyuanita; Saputra, Fazril; Ammar, Esraa E; Akbar, Helmy (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Seagrasses are important marine plants that provide a variety of ecosystem services, including food and shelter for marine life, and protection from coastal erosion. This study investigated the biodiversity (alpha and beta diversity) of seagrass in the Kepulauan Banyak Marine Nature Park, Indonesia, with a specific focus on eight sites. Alpha diversity was calculated using Shannon's index, Simpson's index, and Pielou evenness. Beta diversity was determined using Bray-Curtis dissimilarity and Jaccard dissimilarity allowing us to examine the variations in species composition among different sites. Principal coordinate analysis and Partial distance-based redundancy analysis was used to visualize and investigate the impact of constraint variables to the structure of the seagrass communities. Alpha diversity varied among the sites, with the highest alpha diversity found at the Orongan and Matahari site and the lowest at the Ujung Lolok and Balai sites. The dominant substrate type (mud or sand) was found to be a significant (P≤ 0.01) determinant of seagrass alpha diversity, with mud substrates supporting higher diversity than sand substrates. The relationship between alpha diversity and constrain variables was only significant with closest distance to forest lost and longitude variables. The analysis found that water pH, closest distance to forest lost, mean distance to tourism spots, and closest distance to settlement collectively explained a significant (P≤ 0.001) portion (88.48%) of the variation in beta diversity of seagrass across the sites. The results of this study can be used to develop management strategies for the conservation of seagrass meadows in the park.